Andragogy and Pedagogy as Foundational Theory for Student Motivation in Higher Education - Stephen Pew (Park University, 2007)
How educators approach the issue of student motivation, be it intrinsic or extrinsic, is determined, in part, by the andragogical or pedagogical philosophical underpinnings of professors' teaching practices. Difficulty arises when pedagogical methods and practices are applied in whole or in part to situations that require andragogical dynamics. A misunderstanding or misapplication of these critical issues may result in situational, temporary, or unsustainable models of motivation that guide lifelong learners and perhaps undermine the entire process of student motivation. This discussion explores the root causes of the misapplication of pedagogical models and its impact on adult learners.